The first discovery of the genus Meira Jacquelin du Val outside the western mediterranean area, with description of a new species (Coleoptera, Curculionidae, Entiminae) - Bellò, Cesare; Baviera, Cosimo (Zootaxa, 2014)
A new species of Meira Jacquelin du Val, 1852 from northeast Italy is described: Meira mariaesilvanae sp. n. This is the first discovery of the genus Meira in the northeast of Italy outside the hitherto known distribution. Ecological and distributional data are provided for the new species. Photos of habitus, some morphological details, genitalia and of the type locality illustrate the work. In addition we provide a dichotomous key to Italian species and a checklist to known Meira species.